5x-(4x-x)+2x+4=8x+5

Simple and best practice solution for 5x-(4x-x)+2x+4=8x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(4x-x)+2x+4=8x+5 equation:


Simplifying
5x + -1(4x + -1x) + 2x + 4 = 8x + 5

Combine like terms: 4x + -1x = 3x
5x + -1(3x) + 2x + 4 = 8x + 5

Remove parenthesis around (3x)
5x + -1 * 3x + 2x + 4 = 8x + 5

Multiply -1 * 3
5x + -3x + 2x + 4 = 8x + 5

Reorder the terms:
4 + 5x + -3x + 2x = 8x + 5

Combine like terms: 5x + -3x = 2x
4 + 2x + 2x = 8x + 5

Combine like terms: 2x + 2x = 4x
4 + 4x = 8x + 5

Reorder the terms:
4 + 4x = 5 + 8x

Solving
4 + 4x = 5 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
4 + 4x + -8x = 5 + 8x + -8x

Combine like terms: 4x + -8x = -4x
4 + -4x = 5 + 8x + -8x

Combine like terms: 8x + -8x = 0
4 + -4x = 5 + 0
4 + -4x = 5

Add '-4' to each side of the equation.
4 + -4 + -4x = 5 + -4

Combine like terms: 4 + -4 = 0
0 + -4x = 5 + -4
-4x = 5 + -4

Combine like terms: 5 + -4 = 1
-4x = 1

Divide each side by '-4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| (7x+7b)*(3+1a)= | | 5(f-6)=-10 | | M=12zy | | 10(s-3)=-119 | | 6(s+3)=180 | | 10y=12x | | 3(x+1)-(2x-5)=12 | | -6x-8x+32y-2y+4= | | 0=3(x^2)-30x+63 | | 1x+1=-1x+9 | | 6x+3+5x+10=40 | | y=20+2x | | 3x^2+9-6=0 | | 10x-19=51 | | 2(9s+3)-3s=3(5s+1)-8 | | 1x(x+5)=3x+8 | | X(x+5)=3x+8 | | 200=5(x-55)+50 | | 13x+14y=41 | | 5x+2(x-3)= | | 4(x+8)+3=7x-3(x-5) | | -x^2-5x+12=0 | | 8x-8=8(x+4) | | X^2-3.5x+2.5=0 | | 8x+12=20+4x | | -28+x^2-3x=0 | | x^2+xc+c^2=0 | | 3-2x=21+4x | | 3w+6w=45 | | 2x=14+-4y | | 2x=14+-4 | | ln(x)-ln(x-6)=4 |

Equations solver categories